AVALIAÇÃO DA INFLUÊNCIA DAS ESTRATÉGIAS ADOTADAS POR CIDADES INTELIGENTES NO ASPECTO SOCIAL - ESTUDO DE CASO NO MUNICÍPIO DE VITÓRIA- ES - Borges, Débora dos Santos Rodrigues (2021)
The human factor continues to dominate the core of debates about the complexity of urban centers and, as the core of the discussions, the integration of technological tools developed for personal assistance. In this context, cities called smart tend to seek solutions to urban problems using technology as a means, aiming to achieve a better quality of life for their citizens, associated with the optimization of the management of economic and sustainable resources. Being a Smart City is beyond the ability to ensure the use of technological potential for the management of urban problems, population growth or the accelerated urbanization process. Being a Smart City is also enabling people to integrate different sectors, from the public to the private. However, the accelerated consumption of technologies, without the proper evaluation of the strategies implemented, allows the generation of underutilized and obsolete systems. In addition, loss of data and poorly managed information makes the feedback process unfeasible. The need for transparency in technological actions and systems is fundamental to the integrated urban scenario. However, as the objective of the smart city is based on people, it emerges from the need for an assessment based on the opinion and perception of users. Therefore, the objective of the present work is to evaluate the effective influence of the strategies adopted by Smart Cities in the daily lives of citizens, using the city of Vitória - ES as a case study. The method consisted, from the bibliographic review and considering as a main strategy the application of a questionnaire with the users, in the development of the following steps: definition of the sample; selection and measurement of NBR ISO 37.122 / 2020 indicators; preparation and application of a questionnaire; and comparative analysis of the strategies implemented by the municipality. As a result, aspects were identified that directly impact people's daily lives, real beneficiaries of Smart Cities, so that they can actively create and participate in the solutions and critical issues that arise in complex urban centers, directly impacting the quality of life and local sustainability.